The role of shipbrokers in sustainable maritime clusters: A quantitative approach towards digitalization - Vangelis Tsioumas; Peter J. Stavroulakis; Dionysios Vasilopoulos; Stratos Papadimitriou (Cleaner Logistics and Supply Chain)
Shipbrokers hold a very important role in shipping, as their involvement in bridging supply and demand in the industry is critical. Shipping, a modern yet highly traditional industry, has been woven through the eons of human need for transportation into a highly asymmetric construct with reference to the exchange of information. This pitfall is covered by the reassuring role of the shipbroker and over time can be facilitated only with digitalization. On the other hand, maritime clusters have been considered in previous years as the powerhouses of growth for modern economies, as they can foster national competitive advantages. These constructs have been thought to hold a definitive implication in the aim of the shipping industry towards sustainability. Within this context, the role of shipbrokers has not been documented extensively and this specific research gap is tended to by the present work. This is accomplished through a questionnaire administered to shipping professionals to extract the effect of shipbrokers in clusters, and presented with the utilization of instruments that can play a major part towards a digitalization paradigm. The analysis of the survey results can help attain a definitive image as per the implications of brokers in sustainable maritime clusters.